Green Tea Incorporated Edible Coating Extends the Postharvest Life of Strawberry Fruits (Fragaria ananassa) - Jayamali, N.A.I.; Wijesinghe, Janaka; Silva, P.A.P.M.D. (Advances in Technology, 2022)
In this study, the effects of green tea incorporated edible coating (EC) on the postharvest quality of strawberries were evaluated. EC was prepared by solubilizing carboxymethyl cellulose (0.75 % w/v), glycerol (2% v/v), and green tea concentrate (14% v/v) in distilled water at 80°C. Coated strawberries were packed in perforated polyethylene terephthalate boxes (10 fruits per box) and kept in refrigerated conditions (6±1°C). Uncoated strawberries were used as the control. Significant differences were observed in weight loss, visual quality, titratable acidity, and total soluble solids between the coated and uncoated fruits. The EC significantly reduced the total aerobic plate count and yeast and mold count of the stored fruits (p<0.05). EC exhibited decent in vitro inhibitory activity against Botrytis cinerea. The sensory properties of the coated fruits were comparable with fresh strawberries even on the 15th day of storage. In conclusion, green tea incorporated edible coating can be introduced as an effective coating material for the extension of the postharvest life of strawberry fruits.